Determinan Kesejahteraan Psikologis Pekerja Pertambangan Batubara: Peran Depresi, Kecemasan, dan Stres di PT XYZ, Kalimantan Timur - Iwan Irawan; Indriati Paskarini; Dani Nasirul Haqi (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2026)
Mental health and psychological well-being of workers are important issues in high-risk industries such as coal mining. This study aims to analyze the effect of depression, anxiety, and stress as measured by the Depression Anxiety Stress Scales (DASS) on the psychological well-being of coal mine workers at PT X, East Kalimantan. The research design used was quantitative with a cross-sectional approach on 110 workers. Data were collected using the DASS questionnaire and the psychological well-being scale, and analyzed by multiple linear regression after passing through the classical assumption test. The results of the classical assumption test showed that there was no multicollinearity, heteroscedasticity, or autocorrelation, but the residual distribution was not normally distributed. The regression equation obtained was Y = 3.835 – 0.219Xâ‚ + 0.022Xâ‚‚ – 0.007Xâ‚ƒ. The t-test shows that partially depression, anxiety, and stress do not have a significant effect on psychological well-being (p > 0.05), while the F-test shows that simultaneously the three variables also do not have a significant effect (F count = 0.931; p = 0.429). The coefficient of determination R² = 0.026 indicates that only 2.6% of the variation in psychological well-being is explained by depression, anxiety, and stress, while the remaining 97.4% is influenced by other factors outside the model. These findings imply that efforts to improve the psychological well-being of mine workers should not only focus on reducing symptoms of depression, anxiety, and stress, but should also consider organizational factors, the work environment, and positive psychological resources.